Respon Hidrologi Daerah Aliran Sungai (DAS) Berhutan Jati (Tectona grandis) (Studi Kasus di DAS Cijurey, KPH Purwakarta, PT. Perhutani Unit III Jawa Barat) - H Hendrayanto; Nana Mulyana Arifjaya; Omo Rusdiana; Basuki Wasis; P Purwowidodo (Institut Pertanian Bogor (IPB University), 2001)
The discharge of the upper Cijurey watershed (4.217 km2) was measured using an automatic water level recorder since 1999. The teak (Tectona grandis) plantations of different age classes cover the whole watershed. The watershed is dominated by undulating topography with gentle slopes, low soil permeability and also low potential aquifer flow rate. Hydrograph analysis shows that high peak flow (Qp) reached 32,5 m3/s (1,3 m), while concentration time (Tc) and recession time (Tr) were 2 hours and 3 hours, respectively. Visual observations on stream flow shows that the maximum discharge was more than 2 m high, which caused flood, while for two successive months (August and September, 2000) the river at the watershed out let was totally dry. These hydrograph properties indicated the quite bad hydrological response of the watershed.